Occupational hazards and preventive practices among dentists in Saudi Arabia: A cross sectional survey - Salha H. Huaylah; Tahani Abdullah Al-Qahtani; N.C. Sandeepa (Saudi Dental Journal)
Introduction: Occupational hazard refers to a risk or danger as a result of the nature or working conditions of a particular job. The source of these hazards is the work environment and include physical, chemical, biological, mechanical and social aspects. Dentist is facing hazards like legal and suicidal tendencies too. Assessment of professional hazards among dentists is therefore an important aspect of dental profession.Hence this study was designed to conduct to identify dentists’ perceptions of occupational hazards, preventive measures and to determine whether preventive techniques are employed. Materials & methods: Cross sectional questionnaire based survey was conducted among dentists in Saudi Arabia. Results: Out of 300 responded, 55.3% were male and 44.7% were female. 12.7% had thought about suicide due to the difficulties during occupation and the response was statistically significant among female, Saudi nationality and among GP, Oral Surgeons and Prosthodontist. 50% of respondents had thought of career change prominently reported by females and dentist of more than 20 yrs of practice. Many dentists reported that they have issues like stress due to the work, fatigue and reduced family time. 73.3% reported to have musculoskeletal issues due to the occupation. Only 8.7% dentist follow the position distance rule when barrier is not used. Conclusion: The present research showed that dentist in Saudi Arabia are experiencing significant level of psychological and physical hazard. Though infection control measures were well practiced among respondents, procedures for radiation protection were ignored by many. Based on the results it is noteworthy that effective strategy for lessening occupational hazards should be enhanced among dentist in Saudi Arabia.